Multibody Modeling and Balance Control of a Reaction Wheel Inverted Pendulum Using LQR Controller - Ümit Önen; Abdullah Çakan (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
In this study, modeling and LQR control of a reaction wheel inverted pendulum system is described. The reaction wheel inverted pendulum model is created by using a 3D CAD platform and exported to Simscape Multibody. The multibody model is linearized to derive a state-space representation. A LQR (Linear-quadratic regulator) controller is designed and applied for balance control of the pendulum. The results show that deriving a state-space representation from multibody is an easy and effective way to model dynamic systems and balance control of the reaction wheel inverted pendulum is successfully achieved by LQR controller. Results are given in the form of graphics.